Comparative Effectiveness of 100 mg/kg Levetiracetam Injection in Two Different Epilepsy Models: Temporal Lobe Epilepsy and Genetic Absence Epilepsy - Elif Tuğçe Erdeve; Filiz Onat; Nihan Çarçak (Archives of Epilepsy)
Objective: Levetiracetam (LEV) is a broad-spectrum anti-seizure drug primarily prescribed for partial seizures. We aimed to compare the effects of LEV in two epilepsy models: the kindling model for temporal lobe epilepsy and the Genetic Absence Epilepsy Rats from Strasbourg (GAERS) model for absence epilepsy. Methods: GAERS and Wistar rats underwent stereotaxic surgery for cortical recording electrodes implantation, while bipolar stimulation electrodes were implanted in the right basolateral amygdala of Wistar rats for kindling stimulations. For the kindling procedure, Wistar rats were stimulated at after discharge (AD) threshold twice daily. After three consecutive stage five seizures, the animals were considered kindled and randomly divided into two groups. Kindled animals received intraperitoneal injection of either saline or 100 mg/kg LEV 1 hour before stimulation. Seizure stage, amygdala AD, and total seizure duration were evaluated. GAERS rats were randomly divided into two groups, and spike-and-wave discharges (SWDs) were recorded for 2 hours after intraperitoneally injecting 100 mg/kg LEV or saline. Cumulative SWD duration, number of SWDs, and mean duration of an individual SWD were compared with the saline-treated control group. Results: LEV significantly reduced the seizure severity and AD duration compared to controls. The mean seizure stage was 1.42±0.29 in the LEV group (p<0.0001) while all saline-treated kindled animals reached stage 5 seizure. LEV also lowered the total seizure duration (13.14±1.11 s) significantly compared to vehicle (86.76±12.59 s; p<0.005). In GAERS group, LEV suppressed the SWDs around 40 min after injection, and this anti-seizure effect lasted until the end of a 2-hour electroencephalography recording. Conclusion: LEV, at a dose, 100 mg/kg, effectively reduced convulsive and non-convulsive seizures in two different epilepsy models. These results underscore the efficacy of LEV in mitigating seizure severity and duration across different epilepsy types, suggesting its potential as a promising therapeutic agent for managing both focal and absence seizures.